Cucumber breeding lines are a prospective material for creating new varieties for open ground in southern Russia - O. P. Kigashpaeva; A. V. Gulin; L. P. Lavrova (Овощи России, 2021)
The varieties and hybrids of cucumbers cultivated in the Astrakhan region are insufficiently productive and are largely affected by a number of diseases. The introduction of innovative developments into production, in particular, new varieties and hybrids of domestic selection, largely solves the problem of import substitution and food security. The goal is to use promising breeding lines and their offspring as genetic sources and donors when creating new varieties and hybrids for open field conditions in southern Russia.Methods. Experiments were carried out in the fields of Precaspian agrarian federal scientific center of the Russian academy of sciences, according to the methods used in the Astrakhan region. Within three years, 47 collection samples were tested.Results. The article presents the results of studying the 12 most promising ones, distinguished by a complex of valuable economic traits, in particular by yield, amicability of fruit setting, which are of interest for further breeding work. According to the results of the data obtained, we can say that the best were the lines: 13-88RZ, 13-101RZ, Gherkins, KRASTAVAC, Courage, Zina, they can be used to create new varieties and hybrids of cucumber as donors of a predominantly female type of flowering, harmonious yield.